Fe3+ @ ZnO/polyester based solar photocatalytic membrane reactor for abatement of RB5 dye. (10th February 2020) - Ashar, Ambreen; Bhatti, Ijaz Ahmad; Ashraf, Munir; Tahir, Asif Ali; Aziz, Humera; Yousuf, Maryam; Ahmad, Muhammad; Mohsin, Muhammad; Bhutta, Zeeshan Ahmad
Abstract: Heterogeneous photocatalysis, employing semiconductor metal oxides, especially at nano scale is a promising technique to mortify the dye residues from effluent. The photocatalysts on doping with a suitable dopant can be modified to enhance the photocatalytic activity. In this study, undoped and series of Fe 3+ doped ZnO have been grown on polyester fabric through low temperature hydrothermal method to generate photocatalytic membrane reactors (PMRs). The material grown on the surface of fabric was characterized by XRD, EDX, SEM, TEM, STEM, AFM, XPS, ICP-MS, DRS and PL studies. For ZnO/PMR and Fe 3+ @ZnO/PMR photocatalytic activity was determined and examined to increase for Fe 3+ @ZnO/PMR in the solar region due to the reduction of band gap from 3.2 to 2.6 eV on Fe 3+ doping. The surface properties of PMRs were also determined by zeta potential and contact angle. The characterized ZnO and Fe 3+ @ZnO nano discs based PMRs have been used to degrade RB5 reactive dye on irradiating with artificial sunlight (D65, 72 W). The reaction parameters i.e. initial dye and oxidant concentration, pH and irradiation time have been optimized by Response Surface Methodology (RSM). The extent of dye degradation has been evaluated by UV/vis spectroscopy and FTIR. The maximum degradation achieved was 88.89% for ZnO/PMR and 98.34% for Fe 3+ @ZnO PMR in 180 min. The photocatalytic efficiency of Fe 3+ @ZnO PMR was investigated for 15 batches, with a slight gradual decrease in activity after eight batches. Graphical abstract: Image 1 Highlights: Development of visible light driven photocatalytic membrane reactors. Doping of ZnO with Fe +3 to reduce bandgap for solar light harvesting. Degradation of dyes to treat industrial effluent.